Guillain‐BarrÉ syndrome subtype diagnosis: A prospective multicentric European study - Van den Bergh, Peter Y. K.; Piéret, Françoise; Woodard, John L.; Attarian, Shahram; Grapperon, Aude‐Marie; Nicolas, Guillaume; Brisset, Marion; Cassereau, Julien; Rajabally, Yusuf A.; Van Parijs, Vinciane; Verougstraete, Donatienne; Jacquerye, Philippe; et al. (Muscle & nerve, 2018)
ABSTRACT Introduction: There is uncertainty as to whether the Guillain‐Barré syndrome (GBS) subtypes, acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and acute motor axonal neuropathy (AMAN), can be diagnosed electrophysiologically. Methods: We prospectively included 58 GBS patients. Electrodiagnostic testing (EDX) was performed at means of 5 and 33 days after disease onset. Two traditional and one recent criteria sets were used to classify studies as demyelinating or axonal. Results were correlated with anti‐ganglioside antibodies and reversible conduction failure (RCF). Results: No classification shifts were observed, but more patients were classified as axonal with recent criteria. RCF and anti‐ganglioside antibodies were present in both subtypes, more frequently in the axonal subtype. Discussion: Serial EDX has no effect on GBS subtype proportions. The absence of exclusive correlation with RCF and anti‐ganglioside antibodies may challenge the concept of demyelinating and axonal GBS subtypes based upon electrophysiological criteria. Frequent RCF indicates that nodal/paranodal alterations may represent the main pathophysiology. Muscle Nerve 58: 23–28, 2018.